2022
DOI: 10.3390/ijerph192315709
|View full text |Cite
|
Sign up to set email alerts
|

Spending Money in Free-to-Play Games: Sociodemographic Characteristics, Motives, Impulsivity and Internet Gaming Disorder Specificities

Abstract: Free-to-Play games (F2P) have spread widely all over the world in recent years. The current economic model for these games is based on microtransactions, where gamers can purchase additional items or services inside the game. The aim of the present study was (1) to describe the profiles and gaming patterns of F2P gamers, and (2) to compare F2P gamers who spend money and those who do not, in terms of sociodemographic characteristics, gaming experience, motivations, impulsivity, and risk of Internet gaming disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The insignificant influence of UPPS-P impulsivity traits on problematic Internet gaming may be caused by the small sample size in the study ( N = 109), which was only adequate to detect a modest effect ( r = 0.35) but not weaker correlations [ 7 ]. Costes and Bonnaire [ 15 ] conducted a larger study with 3,472 Free-to-Play gamers showed that all the five UPPS-P impulsivity traits except positive urgency were positively associated with GD, with the Odds Ratios of 1.57–2.9. The varied findings among studies for the association between the UPPS-P impulsivity traits and GD are likely due to the issues of sample size and the type of sample examined.…”
Section: Introductionmentioning
confidence: 99%
“…The insignificant influence of UPPS-P impulsivity traits on problematic Internet gaming may be caused by the small sample size in the study ( N = 109), which was only adequate to detect a modest effect ( r = 0.35) but not weaker correlations [ 7 ]. Costes and Bonnaire [ 15 ] conducted a larger study with 3,472 Free-to-Play gamers showed that all the five UPPS-P impulsivity traits except positive urgency were positively associated with GD, with the Odds Ratios of 1.57–2.9. The varied findings among studies for the association between the UPPS-P impulsivity traits and GD are likely due to the issues of sample size and the type of sample examined.…”
Section: Introductionmentioning
confidence: 99%
“…Gaming has become a very popular activity for both adults and adolescents and a major leisure activity in contemporary societies [5]. Even though most video players are aged between 18 to 34 years old (40%), 27% of players are being overage 50, leading to the average player being 35 years old [6] indicating that there is also a big percentage of players over the age of 35 spending time on video games, and highlighting that players cannot be grouped into one age demographic.…”
Section: Introductionmentioning
confidence: 99%